(untitled) (Research, Society and Development, 2022)
The objective of this work is to analyze the notion of “social” and explain how it relates to the problems inherent to the field of Public Health. Considering the multiplicity inherent to the constructions of such a notion, the study is guided above all by the perspectives of professionals working in the health area. From the methodological point of view, the argument is built from the junction between sociological theoretical reflections and contemporary facts, guided by a certain panorama given by the theme of death. Its results are organized in four axes. Initially, the point of view presented by Émile Durkheim in the work Suicídio is summarized. Then, the customary understanding that humanity would be composed of different “strata”: biological, psychological, social and cultural is discussed. In the sequence, fundamentals of the notion of “social determinants of health” are analyzed. Next, processes linked to the Covid-19 pandemic are pointed out. It concludes by seeking to derive an allegory capable of showing what the “social” would be and its relations with health.